Assessment of stress resistance of educators in wartime conditions depending on the status of displacement (Environment & Health, 2025)
The aim - to assess the manifestation of borderline neurotic disorders among teachers under martial law depending on the status of displacement.Materials and methods. To achieve the goal, the assessment of mental health among teachers was conducted using the methodology «Assessment of mental health in the system of psychosocial support of the population». Respondents were divided into four age groups (up to 30 years old, 31-40 years old; 41-50 years old; over 51 years old); four groups by displacement (non-displaced persons, internally displaced persons within the region, internally displaced persons within the country, internally displaced persons). 364 teachers of secondary education institutions in Sumy were interviewed in the spring of 2024 under martial law.Mathematical processing included the calculation of primary statistical indicators, comparison of samples, and analysis of variance using the standard statistical package STATISTICA 10.0.Results. It was found that teachers with more experience did not change their place of residence, within the Sumy region, mainly young teachers (68.66±2.43)%) moved. Teachers aged 32-40 (8.33±1.45)%, t=3.76, p≤0.01) who had up to 15 years of experience evacuated abroad as internally displaced persons. Within the country teachers aged up to 31 (7.46±1.38)%, t=2.31, p≤0.05) and 41-50 (7.61±1.39%, t=2.38, p≤0.05) moved internally.The dependence of the manifestation of borderline neurotic disorders on age and displacement group was found. In teachers, regardless of the displacement group, the dominant symptom complex is «sleep disturbance» (60.44±2.56) points), however, teachers internally displaced persons within the country (77.27±2.2) points) and internally displaced persons (73.34±2.32) points) have its highest values. Borderline neurotic disorders of teachers without changing their place of residence are characterized by greater manifestations of depression (19.73±2.09) points) and asthenia (18.37±2.03) points). Internally displaced teachers within the region have significantly lower manifestations of depression (9.09±1.51) points), asthenia (6.06±1.25) points). Teachers internally displaced within the country have the lowest manifestations of anxiety (4.55±1.09) points). Internally displaced teachers suffer more from asthenia (13.3±1.78) points) and vegetative disorders (20±2.1) points).Conclusions. The dependence of the manifestation of borderline neurotic disorders on age and displacement group has been established. The dominant symptom complex is «sleep disorders». Borderline neurotic disorders of teachers without changing their place of residence are characterized by greater manifestations of depression and asthenia; internally displaced teachers within the region probably have lower manifestations of depression, asthenia; internally displaced teachers suffer more from asthenia and vegetative disorders than others.
Keywords: somatic health; mental health; borderline neurotic disorders; displacement groups; martial law; teachers